2019
DOI: 10.2478/jce-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Plaque Geometry and Thoracic Fat Distribution in Patients with Acute Chest Pain – a CT Angiography Study

Abstract: The aim of our study was to investigate the correlation between volumes of thoracic fat distributed in different compartments and the geometry of vulnerable coronary plaques assessed by coronary computed tomography angiography (CCTA), in patients with acute chest pain. Methods: This was a non-randomized, observational, single-center study, including 50 patients who presented in the emergency department with acute chest pain who underwent 128-slice single-source CCTA. Plaque geometry was evaluated in transversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…We applied robust methodology: CT acquisition and assessment followed standard methods and cardiac adipose tissue was automatically quantified using the cardiac software, Syngo.via Frontier [26,27]. The volumes of cardiac adipose tissue observed in this study were consistent with those previously reported [6,[28][29][30].…”
Section: Study Limitationssupporting
confidence: 84%
“…We applied robust methodology: CT acquisition and assessment followed standard methods and cardiac adipose tissue was automatically quantified using the cardiac software, Syngo.via Frontier [26,27]. The volumes of cardiac adipose tissue observed in this study were consistent with those previously reported [6,[28][29][30].…”
Section: Study Limitationssupporting
confidence: 84%
“…Non-calcified, partially calcified, and calcified plaques could be extracted separately based on their attenuation values (Daghem et al, 2020). Therefore, CCTA has been widely applied in the analysis of coronary plaque geometry (Rinehart et al, 2011;Ratiu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently suggested that the adipose tissue may play a significant role in the complex process of atheromatous plaque progression and destabilization [2]. Adipose tissue is a tissue present throughout the body and has multiple roles in the complex thermoregulation process.…”
Section: Introductionmentioning
confidence: 99%